Study of the use of quality tools to analyze the root cause of low service performance in a telecommunication company - Silva, Catala Racile Ruela; Souza Junior, Wilson Rodrigues de (Brazilian Journal of Production Engineering, 2022)
The systematic approach to problems is one of the most important aspects of a quality program. Several tools were developed to help professionals understand the problems that occur in their daily lives, find the root cause and find adequate solutions for them. The proposed work aimed to apply tools from the quality management area, working on all aspects of problem solving, to find the root cause of the poor customer service evaluation, in order to improve the satisfaction score (customer service assessment) of a customer service campaign. Among the tools that were used are: Pareto chart, cause and effect diagram, GUT matrix and 5W2H. The result found was continuous improvement actions that will contribute to improving the operation indicator, confirming the objective of quality management, total customer satisfaction.